International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.1989.266479
|View full text |Cite
|
Sign up to set email alerts
|

Speaker verification over long distance telephone lines

Abstract: In this paper we present the results of speaker verification technology development for use over long distance telephone lines. We describe two large speech databases that were collected to support the development of new speaker verification algorithms. We discuss the results of discriminant analysis techniques which improve the discrimination between true speakers and impostors. We compare the performance of two speaker verification algorithms, one using template based Dynamic Time Warping (DTW) and the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…Matching is usually done by evaluating the likelihood of the test utterance with respect to the model. The Gaussian mixture model (GMM) [198,197] and the hidden Markov model (HMM) [19,171] are the most popular models for text-independent and textdependent recognition, respectively.…”
Section: Speaker Modelingmentioning
confidence: 99%
“…Matching is usually done by evaluating the likelihood of the test utterance with respect to the model. The Gaussian mixture model (GMM) [198,197] and the hidden Markov model (HMM) [19,171] are the most popular models for text-independent and textdependent recognition, respectively.…”
Section: Speaker Modelingmentioning
confidence: 99%
“…Speaker recognition systems based on an HMM architecture used speaker models derived from a multi-word sentence, a single word, or a phoneme. Typically, multi-word phrases (a string of seven to ten digits, for example) were used, and models for each individual word and for "silence" were combined at a sentence level according to a predefined sentence-level grammar [34]. (4) VQ/HMM-based text-independent methods: Nonparametric and parametric probability models were investigated for text-independent speaker recognition.…”
Section: Smentioning
confidence: 99%
“…Besacier and Bonastre found that certain sub-bands contained more speaker-specific information than others: in particular, the low-frequency region below 600 Hz and the high-frequency region above 2 kHz. This helps to explain the poorer performance rates for telephone-quality speech (e.g., Naik, Netsch, and Doddington 1989), where some of these critical high and low frequency regions are absent.…”
Section: Previous Work On Sub-band Processingmentioning
confidence: 99%